Extensive genetic differentiation between recently evolved sympatric Arctic charr morphs - Guðbrandsson, Jóhannes; Kapralova, Kalina H.; Sigrídur Franzdóttir; Bergsveinsdóttir, Þóra Margrét; Hafstað, Völundur; Jónsson, Zophonías O.; Snorrason, Sigurður S.; Palsson, Arnar (figshare, 2019)
Supplementary material for the paper "Extensive genetic divergence between recently evolved sympatricArctic charr morphs" by Jóhannes Guðbrandsson, Kalina H. Kapralova, Sigríður R. Franzdóttir, Þóra Margrét Bergsveinsdóttir, Völundur Hafstað, Zophonías O. Jónsson, Sigurður S. Snorrason and Arnar Pálsson.